Resilience Analysis of Multi-Modal Transportation Networks: A Case Study of the Beijing-Tianjin-Hebei Region - Shuyan Zheng; Ye Zhang; Yanyan Chen (Journal of Highway and Transportation Research and Development)
The efficient, reliable, and sustainable nature of a transportation system is a prerequisite to support the development of urban agglomeration. This paper proposes network modeling and resilience assessment methods for public transportation in urban agglomerations. A multi-layer network is constructed. With the identification of the key nodes in a multi-modal transportation network (MMTN), a resilience assessment method is proposed that considers two phases: absorption and recovery after an attack. The Beijing-Tianjin-Hebei urban agglomeration network is taken as a case study. The results show that the attack on key nodes brings more influence to MMTN than random attacks. More attention is suggested to be paid to the larger hub-type stations in operation and management. The proposed method can be applied in different types of urban agglomerations and serve as technical support for reducing the disorder and imbalance of MMTN.